Skeletal muscle mass: evaluation of neutron activation and dual-energy X-ray absorptiometry methods - Wang, Z M; Visser, M; Ma, R; Baumgartner, R N; Kotler, D; Gallagher, D; Heymsfield, S B (Journal of applied physiology (1985), 1996)
Although skeletal muscle (SM) is a major body component, whole body measurement methods remain limited and inadequately investigated. The aim of the present study was to evaluate the Burkinshaw in vivo neutron activation analysis (IVNA)-whole body 40K-counting and dual-energy X-ray absorptiometry (DXA) methods of estimating SM by comparison to adipose tissue-free SM measured using multiscan computerized axial tomography (CT). In the Burkinshaw method the potassium-to-nitrogen ratios of SM and non-SM lean tissue are assumed constant; in the DXA method the ratio of appendicular SM to total SM is assumed constant at 0.75. Seventeen healthy men [77.5 +/- 13.8 (SD) kg body wt] and eight men with acquired immunodeficiency syndrome (AIDS; 65.5 +/- 7.6 kg) completed CT, IVNA, and DXA studies. SM measured by CT was 34.4 +/- 6.2 kg for the healthy subjects and 27.2 +/- 4.0 kg for the AIDS patients. Compared with CT, the Burkinshaw method underestimated SM by an average of 6.9 kg (20.1%, P = 0.0001) and 6.3 kg (23.2%, P = 0.01) in the healthy men and the men with AIDS, respectively. The DXA method minimally overestimated SM in both groups (2.0 kg and 5.8% in healthy men, P = 0.001; 1.4 kg and 5.1% in men with AIDS, P = 0.16). This overestimate could be explained by a higher actual than assumed ratio of DXA-measured appendicular SM to total body SM (actual = 0.79 +/- 0.05, assumed = 0.75). The current study results reveal that large errors are present in the Burkinshaw SM method and that substantial refinements in the models that form the basis of this IVNA approach are needed. The model on which the DXA-SM method is based also needs further minor refinements, but this is a promising in vivo approach because of less radiation exposure and lower cost than the IVNA and CT methods.